Demographic characteristics and viewing habits in reference to the soap opera "Mari Mar" among residents of Barangay Trapiche, Oton, Iloilo. - Java, Lynie J.
This study entitled "Demographic characteristics and television viewing habits in reference to the soap opera " Mari Mar ", aims to find out the relationship between demographic characteristics and a person's viewing habits as indicated by the frequency, length and time of watching the soap opera "Mari Mar"., The researchers made use of multi-stage sampling using the simple random survey method. A survey was conducted within a barangay. The population size was composed of 1,364 voting residents. Five percent representing 68 persons were taken as sample respondents. A questionnaire checklist was used to solicit data about the respondent's personal demographics and viewing habits in reference to the soap opera " Mari Mar". Chi-square test at 0.05 level of significance was used to determine the relationship between demographic characteristics and person's viewing habits as indicated by the frequency, length and time watching, hence, chi-square test was performed for each indicator independently. Results showed that generally, there is no significant relationship between age and viewing habits of a person; civil status has no relationship with the viewing habits of a person. However, chi-square test between the relationship of education and person's viewing habits revealed a noted relationship particular only to the length of watching. Findings showed that majority of the "college-educated" respondents do not watch the show in full length which is 45 minutes. Likewise, a noted relationship between a person's occupation and time of watching is evident in this study. It was found out that majority of the "white collar" workers do not catch the start of "Mari Mar" at 6:30 they were regarded as late "viewers". Also some degree of relationship is evident between gender and time of watching. This result cannot be regarded strictly at all times because it is obvious that in this study, number of females composed a large majority of the total number of respondents hence, affecting the result of the data.